PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN APLIKASI CANVA PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV SD - Nurmah Dalizah; Safrida Napitupulu (Bajang Institute, 2024)
This research aims to develop learning media assisted by the Canva application that is suitable for use in the thematic learning process on the theme